Respons Karakter Fisiologis Tanaman Karet (Hevea brasiliensis Muell. Arg) Klon BPM 24 terhadap Konsentrasi dan Jenis Stimulan Etilen Organik Kulit Pisang - Syamsiyah Syaher; Cucu Suherman; Santi Rosniawaty; Fetrina Oktavia (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2020)
The peak production of BPM 24 clone rubber was reached in the 7th to 10th year, but production quickly declined to reach its lowest point in 15 years. Stimulants are technologies used to increase production. Stimulants generally contain ethylene. Ethylene affects the balance of sucrose in latex formation and also increases metabolic activity in latex vessel cells. The purpose of this study is to know the physiological character response of rubber plants (hevea brasiliensis Muell. Arg) clone BPM 24 against the application of organic ethylene stimulant banana peel. The research was conducted in september to november 2019 at the research center of rubber experimental garden Sumbawa in Palembang, South Sumatra. This research method is descriptive with treatment: without stimulant, ethrel 10 PA, banana peel Ambon concentration 333 g/L, banana peel Ambon concentration 500 g/L, banana peel Ambon concentration 666 g/L, banana skin wax concentration 333 g/L, banana skin wax concentration 500 g/L, banana skin wax concentration 666 g/L, banana peel Kepok concentration 333 g/L, banana peel Kepok concentration 500 g/L, banana peel Kepok concentration 666 g/L. Observations are carried out on physiological character (thiol levels, inorganic phosphate levels, sucrose levels and dry tapping grooves. The treatment of banana skin stimulant is able to increase the production of latex without interference in the physiological character of the plant, but the use of stimulants with excessive and inappropriate doses can lead to the onion of dry tapping grooves.